1993
DOI: 10.1210/jcem.77.6.8263152
|View full text |Cite
|
Sign up to set email alerts
|

Normal basal and insulin-stimulated fuel metabolism in lean women with the polycystic ovary syndrome.

Abstract: Many reports have suggested that hyperandrogenaemic patients with the polycystic ovary syndrome (PCOS) may be insulin resistant. However, there have also been suggestions that their insulin resistance may relate to obesity and android fat distribution. To assess whether PCOS induces metabolic disturbances independently of obesity, we studied seven lean patients with PCOS (age, 27.1 +/- 2.0 yr; body mass index, 22.2 +/- 0.78 kg/m2; waist/hip ratio, 0.79 +/- 0.02; fat-free mass, 46.38 +/- 1.13 kg) and seven norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 27 publications
3
25
0
5
Order By: Relevance
“…However, prevalence data on IR in PCOS are inconsistent and influenced by multiple factors including study population, evaluation methods of insulin sensitivity, BMI, family history of diabetes, and diagnostic criteria for PCOS (31,(36)(37)(38)(39)(40). In particular there has been some incongruent results regarding the lean group of women with PCOS, who may not be as insulin resistant as the obese counterpart, but may be more insulin resistant than lean women without PCOS (38). Results on this issue may also be hampered by the use of many different phenotypes of PCOS, which may, not all, be predictors of IR.…”
Section: Discussionmentioning
confidence: 99%
“…However, prevalence data on IR in PCOS are inconsistent and influenced by multiple factors including study population, evaluation methods of insulin sensitivity, BMI, family history of diabetes, and diagnostic criteria for PCOS (31,(36)(37)(38)(39)(40). In particular there has been some incongruent results regarding the lean group of women with PCOS, who may not be as insulin resistant as the obese counterpart, but may be more insulin resistant than lean women without PCOS (38). Results on this issue may also be hampered by the use of many different phenotypes of PCOS, which may, not all, be predictors of IR.…”
Section: Discussionmentioning
confidence: 99%
“…And whereas obesity increases insulin resistance, lean women with PCOS have the same level of insulin sensitivity as obese controls (99, 104, 283), or in some cases lean controls (284,285). The reason for not detecting differences in insulin sensitivity in lean women with PCOS might be explained by racial/ethnic differences, and this warrants further investigation (286,287). Women with 1990 NIH-defined PCOS, which includes HA, have greater insulin resistance compared to anovulatory women with PCOS who have normal androgen levels and are relatively healthier metabolically (288 -290), whereas a relatively normal weight (BMI Ͻ 27 kg/m 2 ) significantly ameliorates this metabolic risk (134,291).…”
Section: E Insulin Sensitivity and Secretionmentioning
confidence: 99%
“…Several studies using the euglycemic hyperinsulinemic clamp showed that insulin resistance was consistently present in obese PCOS women, however, the results have been conflicting in lean women with PCOS [8][9][10][11][12][13]. Moreover, the role of insulin resistance as a risk factor for the development of glucose intolerance has still not been clearly defined in women with PCOS.…”
Section: Introductionmentioning
confidence: 99%